Peran Keluarga Pendiri Dalam Menciptakan Kinerja Keuangan Dan Nilai Pasar Perusahaan Pada Perusahaan Keluarga - Dewi Ariani; Noorlaily Fitdiarini (Universitas Airlangga, 2014)
This study objective is to understand the effect involvement of founder family to financial performance (ROA) and firm market value (Tobins Q) in family firm which is listed in BEI (Bursa Efek Indonesia). Data obtain from annual reports and daily stock price which is publish between 2008 until 2013. Sample of this study included 33 family firm and 198 observation with purposive random sampling. This study use multiple linier regression method to test the effect of founder as an independent variable and control variables which is contain size, age and risk, towards firm financial performance (ROA) and firm market value (Tobins Q) as dependent variables. The result suggest that involvement of founder family has significant negative effect towards ROA and Tobins Q. This result show that family firm which managed by founder family tend to have smaller financial performance and firm market value.